Helicobacter suis Is Associated With Mortality in Parkinson's Disease - Augustin, Aisha D.; Savio, Antonella; Nevel, Amanda; Ellis, Richard J.; Weller, Clive; Taylor, David; Tucker, Rosalind M.; Ibrahim, Mohammad A. A.; Bjarnason, Ingvar; Dobbs, Sylvia M.; Dobbs, R. John; Charlett, André (Frontiers in Medicine, 2019)
Helicobacter pylori has been implicated in the pathogenesis of Parkinson’s disease (PD). Its eradication, in a randomised placebo-controlled trial, improved PD hypokinesia. Helicobacter species zoonosis might explain excess mortality from PD and non-Hodgkin lymphoma in livestock, but not arable, farmers. Indeed, Helicobacter is causally-associated with gastric lymphoma. We have previously shown that the relative-frequency, H. suis to H. pylori, was 10-times greater in 60 PD-patients than in 256 controls. We now go on to evaluate the pathological significance of H. suis, detected in gastric-biopsy DNA-extracts by ureA-based species-specific qPCR, validated by amplicon sequencing. The methodology had been cross-validated by a carR-based PCR. The pathological significance is put in context of H. pylori detection [urea-breath-test (UBT) with biopsy-culture, and, if negative, PCR], and potential reservoir in pigs. Here, we explore, in these 60 PD-patients, associations of H. suis status with all-cause-mortality, and with orthostatic cardiovascular and blood profiling. H. suis had been detected in 19 of the 60 PD-patients on one or more occasion, only two (with co-existent H. pylori) being urea breath test (UBT) positive. We found that the hazard-of-death (age-at-diagnosis- and gender-adjusted) was 12 (95% CI 1, 103) times greater (likelihood-ratio test, P=0.005) with H. suis-positivity (6/19) than with negativity (2/40: one lost to follow-up). UBT-values did not influence the hazard. H. suis-positivity was associated with lower standing mean-arterial-pressure (6 (1, 11) mmHg), H. pylori-positivity having no effect. The lower total lymphocyte count with H. pylori-positivity (-8 (-1, -14) %) was not seen with H. suis, where T-cell counts were higher (24 (2, 52) %). Regarding the potential zoonotic reservoir in the UK, Helicobacter-like-organism frequency was determined in freshly-slaughtered pigs, nature ascertained by sequencing. Organisms immunostaining for Helicobacter, with corkscrew morphology typical of non-H. pylori Helicobacter, were seen in 47% of 111 pig-antra. We conclude that H. suis is associated with all-cause-mortality in PD and has a potential zoonotic reservoir.